Calcium antagonism and the vasorelaxation of the rat aorta induced by rotundifolone - Guedes,D.N. (2004)
The vasorelaxing activity of rotundifolone (ROT), a major constituent (63.5%) of the essential oil of Mentha x villosa, was tested in male Wistar rats (300-350 g). In isolated rat aortic rings, increasing ROT concentrations (0.3, 1, 10, 100, 300, and 500 µg/ml) inhibited the contractile effects of 1 µM phenylephrine and of 80 or 30 mM KCl (IC50 values, reported as means ± SEM = 184 ± 6, 185 ± 3 and 188 ± 19 µg/ml, N = 6, respectively). In aortic rings pre-contracted with 1 µM phenylephrine, the smooth muscle-relaxant activity of ROT was inhibited by removal of the vascular endothelium (IC50 value = 235 ± 7 µg/ml, N = 6). Furthermore, ROT inhibited (pD2 = 6.04, N = 6) the CaCl2-induced contraction in depolarizing medium in a concentration-dependent manner. In Ca2+-free solution, ROT inhibited 1 µM phenylephrine-induced contraction in a concentration-dependent manner and did not modify the phasic contractile response evoked by caffeine (20 mM). In conclusion, in the present study we have shown that ROT produces an endothelium-independent vasorelaxing effect in the rat aorta. The results further indicated that in the rat aorta ROT is able to induce vasorelaxation, at least in part, by inhibiting both: a) voltage-dependent Ca² channels, and b) intracellular Ca2+ release selectively due to inositol 1,4,5-triphosphate activation. Additional studies are required to elucidate the mechanisms underlying ROT-induced relaxation.